2009
DOI: 10.3899/jrheum.090273
|View full text |Cite
|
Sign up to set email alerts
|

Unresponsiveness to Colchicine Therapy in Patients with Familial Mediterranean Fever Homozygous for the M694V Mutation

Abstract: Our results indicate that the M694V/M694V mutation is associated with lower response to colchicine treatment. Therefore, patients homozygous for M694V/M694V may be carrying an increased risk for development of amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 47 publications
4
27
1
2
Order By: Relevance
“…Only minimal genotype/phenotype correlations have emerged, and we tend not to draw much attention to them with our patients, as we feel that the exact MEFV mutation is not the sole determinant of clinical severity or colchicine response. 2 Homozygosity for the M694V mutation has been associated with relative resistance to colchicine, 10 and we have observed this occasionally as well. Similarly, certain mutations are said to be more associated with amyloidosis than others.…”
Section: Molecular Genetic Testingsupporting
confidence: 69%
“…Only minimal genotype/phenotype correlations have emerged, and we tend not to draw much attention to them with our patients, as we feel that the exact MEFV mutation is not the sole determinant of clinical severity or colchicine response. 2 Homozygosity for the M694V mutation has been associated with relative resistance to colchicine, 10 and we have observed this occasionally as well. Similarly, certain mutations are said to be more associated with amyloidosis than others.…”
Section: Molecular Genetic Testingsupporting
confidence: 69%
“…Recently, Omenetti et al [17] have showed that IL1 secretion increased with both the number and penetrance of mutations, confirming the studies showing increased requirement of colchicine dosage and unresponsiveness in patients with homozygous M694V [18,19].…”
Section: Discussionmentioning
confidence: 77%
“…AAA patogenezinde TNF-α'nın rolünün aydınlatılması ile birlikte kolşisine yanıtsız hastalarda TNF-α blokerleri denenebilir. 8 Oral kolşi-sine yanıt vermeyen hastalarda anti TNF-α ajanların kullanımı konusunda sınırlı sayıda vaka bildirilmiştir.…”
Section: Discussionunclassified